The value of firm networks: A natural experiment on board connections - Ester Faia; Maximilian Mayer; Vincenzo Pezone (Leibniz Institute for Financial Research SAFE, 2021)
We present causal evidence on the e↵ect of boardroom networks on firm value and compensation policies. We exploit a ban on interlocking directorates of Italian financial and insurance companies as exogenous variation and show that firms that lose centrality in the network experience negative abnormal returns around the announcement date. The key driver of our results is the role of boardroom connections in reducing asymmetric information. The complementarities with the input-output and cross-ownership networks are consistent with this channel. Using hand-collected data, we also show that network centrality has a positive e↵ect on directors' compensation, providing evidence of rent sharing.
Keywords: D57; G14; G32; L14; 330; Firm Networks; Natural Experiment; Executives' Compensation; Interlocking Directorates